A evoluç\~ao do crédito no Brasil entre 2003 e 2010 - Mônica Mora de Araujo de Couto e Silva (Instituto de Pesquisa Econômica Aplicada (IPEA), 2014)
– The credit increased expressive and continuously throughout the Lula government, even after the 2008 crisis. This study aims to analyze this process and its determinants. We identify two different periods. We concluded that changes in legislation as well as financial innovations, in a favorable macroeconomic context, affected credit and contributed to explain the increase of supply of credit with free resources between 2004 and 2008. In 2009 and 2010 deliberate government decision to increase credit with targeted resources and free resources in order to sustain the supply of credit (or, at least mitigate its fall) allowed to understand the behavior of credit after the outbreak of financial crisis in 2008.
Keywords: E44; E51; 330; credit; Brazilian economy